Neactaeonina argentina, new species, and family placement of the genus Neactaeonina thiele, 1912 (Mollusca: Gastropoda) - Zelaya, D.G. (2011)
Neactaeonina argentina, a new species from the outer Argentine shelf off Buenos Aires province, is described. The species is characterized by the elongate, low-spired shell, with shouldered, nearly straight whorls, deep suture, and sculpture composed of numerous, broad, flat spiral cords. The radula is similar to that previously described for the type species, Neactaeonina cingulata Thiele, 1912, except in having a greater number of teeth. The present study provides the first information on the anatomy and histology of the genital system, and details of the radula anatomy of Neactaeonina, both unknown to date. The study of anatomical characters demonstrates that Neactaeonina has clear similarities with other Acteonidae, with a combination of features present in Acteon (such as the presence of a strongly calcified shell, with well-developed operculum; mantle cavity opening anteriorly; nervous system with only the cerebropleural ganglia fused; a single allosperm sac associated with the female system; radula without cardinal tooth; and oral cuticle with rod-like processes); and some characters present in acteonid genera other than Acteon (e.g., the number and morphology of teeth, and processes of the oral cuticle). However, Neactaeonina shows some characters thus far not reported for any other genus currently placed into the Acteonidae: salivary glands with laminar structure, male genital system with an open portion, a single allosperm sac opening distally, and a flat and triangular copulatory organ.